(untitled) (Journal of the College of Basic Education, 2022)
This study aimed to find out the level of scientific enlightenment of science teachers and its relationship to the scientific thinking skills of their students. The sample of the study consisted of (32) primary schools that were chosen in a random stratified manner from mixed primary schools belonging to the center of the General Directorate of Education of Karkh II. The sample of the study constituted (34%) of the community, and a male or female teacher was chosen from each school. Thus, the sample of teachers reached 32 male and female teachers. A class was chosen for each teacher, and thus the sample of students reached (1025) male and female students.